Structural Particularities of Gall Neoformations Induced by Monarthropalpus flavus in the Leaves of Buxus sempervirens - Irina Neta Gostin; Irinel Eugen Popescu; Cristian Felix Blidar (Plants)
The boxwood leafminer Monarthropalpus flavus (Diptera, Cecidomyiidae) has historically been considered a leafminer, but some researchers suggested it induced galls on Buxus species leaves. The larvae of M. flavus create small blister-like galls on Buxus sempervirens leaves, causing tissue hypertrophy and hyperplasia. Histological examination reveals that M. flavus larvae cause the formation of small blister galls, which involve tissue reorganization in the mesophyll. Unlike typical leafminers, which only disrupt existing tissues, M. flavus induces the appearance of a neo-formed tissue, near the larval chamber. This tissue, originating primarily from spongy parenchyma cells, significantly increases as the leaf thickens. Various histochemical analyses show that the new tissue contains starch, lipids, terpenes, and proteins, providing evidence of reprogramming in the plant’s metabolism. The study concludes that M. flavus induces rudimentary galls, not simply mines, due to the formation of new tissue, whose cells have cytological characteristics distinct from those found in non-galled leaves. However, despite some gall-like features, it does not create new vascular elements, distinguishing it from more complex galls formed by other gall-inducing species.